Design like you give a damn architectural responses to humanitarian crises (Thames & Hudson, 2006)
" Edited by architecture for Humanity, a volunteer-based organization that provides architectural solutions to humanitarian crises, Design Like You Give a damm brings the best of humanitarian design to the printed page. Proceeds from the sale of this book will support the work of Architecture for Humanity."